Successful utilization of blood purification therapy with Oxiris® haemofilter for the management of severe leptospirosis with multiorgan involvement: a case report - Azmi, Nurul Izzah; Abdul Rahim, Shahir Asraf; Md Ralib, Azrina (Malaysian Society of Anaesthesiology, 2023)
Severe leptospirosis is associated with excessive proinflammatory and anti-inflammatory cytokines that lead to multiorgan failure. Oxiris® haemofilter is a blood purification therapy that can be utilized to control these inflammatory responses during early phase of sepsis-associated acute kidney injury (AKI) that requires renal replacement therapy. We present a case of a 15-year-old male with severe leptospirosis with multiorgan involvement who was admitted to our intensive care unit (ICU). He had septic shock with myocarditis, respiratory failure, AKI with metabolic acidosis, and transaminitis. We started him on continuous veno-venous haemofiltration with the Oxiris haemofilter for metabolic acidosis and cytokine absorption for a total duration of 35 hours. A rapid decrease of vasopressor requirement, lactate, and procalcitonin levels was observed following therapy initiation. He was extubated on day 5 of ICU admission and discharged well to the general ward after 7 days in the ICU. This case highlights the potential benefits of the Oxiris haemofilter as an adjunct in the management of septic shock in severe leptospirosis with multiorgan involvement. Randomized clinical trials are warranted to validate the clinical benefits of this therapy.